AKTIVITAS PEMBELAJARAN DALAM JARINGAN (DARING) PADA MASA PANDEMI COVID-19 MAHASISWA ANGKATAN 2020 PROGRAM STUDI PENDIDIKAN GEOGRAFI FKIP UNDANA KUPANG - Samin, Mikael; Hasan, Muhammad Husain (Jurnal Geografi, 2021)
In the conditions of the Covid-19 pandemic, learning was more emphasized online based so that it undergoes many changes and adaptations by both lecturers and students. This research aimed to find out how online learning activities were during the Covid-19 pandemic, 2020's grade students of the Geography Education Program, FKIP Undana Kupang. The method used in this study was a descriptive method with a qualitative approach. Data collection techniques used interviews and observations. Data analysis used includes data reduction (summarizing/choosing the main points), data display, and conclusions. The results showed 1). The advantages of online learning were the flexibility of space and time by utilizing online learning applications, namely Zoom, Google Meet, Google Classroom, Undana E-Learning, and WhatsApp; 2). The main obstacle to learning in the network is the stability of the internet network in various places and the high cost of internet data packages; 3). Student learning outcomes as far as the lecturers observed were still good, only the values are given require wisdom from the lecturers who were in charge of the course